Characterization of Bonga and Horro indigenous sheep breeds of smallholders for designing community based breeding strategies in Ethiopia - Edea, Zewdu (Haramaya University, 2008)
In the framework of designing community-based breeding strategies for indigenous sheep breeds of smallholders in Ethiopia, a survey of production system and on-farm characterization of Horro and Bonga sheep breeds, was undertaken in the Horro and Adiyo Kaka districts, respectively. Purposive and random sampling was employed as sampling technique. Detailed structured questionnaires, focus group discussions, field observations of animals, body measurements, and secondary data collection were employed to produce the data. Body weight, linear body measurements, and qualitative records were taken and observed from 762 Bonga sheep and 816 Horro sheep. For the analyses of quantitative data, the main effects of breed and dentition were fitted to the model within each sex groups. Results revealed that the mean flock sizes for Adiyo Kaka and Horro districts were 11.28 ± 1.27and 8.20 ± 2.05, respectively. Sheep have multi-purpose roles in both production systems. Among the reasons for keeping sheep, source of income was ranked highest. Age at first lambing for Bonga and Horro sheep was 14.9 ± 3.1 and 13.3 ± 1.7 months, respectively. Average lambing intervals were 8.9 ± 2.1 and 9.2 ± 2.4 months, for Bonga and Horro, respectively. Disease, feed shortage, and predators were the most pertinent constraints for sheep production in that order for farmers in Horro. In Adiyo Kaka, disease, labor shortage, predators were ranked as first, second and third based upon their significant influence on sheep productivity. The mean body weight, body length, chest girth, wither height, tail circumference and tail length for Bonga females were 31.87 ± 0.19kg, 69.16 ± 0.15 cm, 72.92 ± 0.17cm, 68.12 ± 0.14cm, 15.92 ± 0.30 cm and 32.07 ± 0.37 cm, respectively. The corresponding values for males of the same breed were 29.70 ± 1.17kg, 68.27 ± 0.89cm, 70.0 ± 1.026cm, 66.53 ± 0.85cm, 20.85 ± 0.97cm and 35.40 ± 0.96cm, respectively. For Horro females, the values in the same order were 27.65 ± 0.21, 67.40 ± 0.164cm, 73.81 ± 0.19cm, 69.43 ± 0.16cm, 16.08 ± 0.15cm and 37.52 ± 0.95, respectively. The values of the measurements for males, on the other hand, were 31.66 ±1.23kg, 69.30 ± 0.94cm, 76.12 ±1.08cm,71.66± 0.90cm,23.46±0.97cm and 37.52 ± 0.95cm,respectively.Within each sex, it was found that breed had significant effect on live body weight and most of the body measurements. Accordingly, Horro females had significantly (P<0.01) greater values for chest girth, wither height and tail length than Bonga females. On the contrary, Bonga ewe’s had significantly (P<0.01) higher values than Horro with respect to body weight, body length, chest width, pelvic width and ear length. Horro male had higher values (P< 0.01) for chest girth; wither height and scrotal circumference than Bonga males. With the exceptions of ear length, tail circumference, tail length and body condition score, within the range of age studied, age was found to have a significant influence (P< 0.01) on most body measurements in females. The mean body weight and body measurements of animals at dentition 1 and 2 were significantly lower than those of the dentition class 3 to 4-years-old sheep. The correlations between body weights and body measurements at different ages were positive and significant (P<0.01). The highest correlation coefficient was found between body weight and chest girth in both of the breeds, sexes, and age groups. The regression analysis to predict body weight from linear measurements indicated that body weight, in most of the cases, could be predicted with a higher level of accuracy from more than one independent trait. However, for practical point of view, the use of chest girth as estimator variable for body weight was suggested due to ease of measurement under farmers’ conditions. To realize full benefits of the forthcoming breeding strategies, concurrent improvement in the nongenetic factors (disease and feed) is central. ===